10, 000 steps a day? Activity trackers, health information literacy and the potential role of Information Science & Health Libraries. (21st September 2021) - Imeri, Aylin
Abstract: Acknowledging the new ways in which activity tracking technologies (ATTs) such as Apple Watch, Fitbit and Garmin are changing the ways in which we understand human‐information interactions, Aylin Imeri calls for information science and health libraries to extend their health information literacy remit to support ATT user information needs.